2007
DOI: 10.1039/b613793h
|View full text |Cite
|
Sign up to set email alerts
|

An enzymatic method for site-specific labeling of recombinant proteins with oligonucleotides

Abstract: DNA was site-specifically conjugated to a substrate peptide of microbial transglutaminase fused to the N- or C-terminus of target proteins without the loss of the proteins' functions of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 30 publications
0
53
0
3
Order By: Relevance
“…[15,16] Our previous research revealed that the stable and Ca 2 + -independent TGase from Streptomyces mobaraensis (microbial TGase, MTG) [17,18] effectively catalyzes the 1:1 cross-linking reaction of a K-tagged enzyme to a 5'-end Q-labeled oligonucleotide. [12] In the present research, an acyl-donor substrate of MTG, benzyloxycarbonyl-l-glutaminylglycine A C H T U N G T R E N N U N G (Z-QG) [19][20][21] was coupled to the primary amino group of 5-(3-aminoallyl)-2'-deoxyuridine-5'-triphosphates (AA-dUTP) by an amide linkage ( Figure S2 in the Supporting Information) to obtain 5-[3-(Z-Gln-Gly-amido)-1-(E)-propenyl]-2'-deoxyuridine 5'-triphosphate (Z-QG-dUTP, Scheme 1), and to subsequently prepare Z-QG-modified DNA by using the polymerase chain reaction (PCR). A UV-absorbance spectrum of Z-QG-dUTP showed absorbance maxima at 240 and 296 nm, which are representative of a pyrimidine ring modified with an exocylic double bond.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…[15,16] Our previous research revealed that the stable and Ca 2 + -independent TGase from Streptomyces mobaraensis (microbial TGase, MTG) [17,18] effectively catalyzes the 1:1 cross-linking reaction of a K-tagged enzyme to a 5'-end Q-labeled oligonucleotide. [12] In the present research, an acyl-donor substrate of MTG, benzyloxycarbonyl-l-glutaminylglycine A C H T U N G T R E N N U N G (Z-QG) [19][20][21] was coupled to the primary amino group of 5-(3-aminoallyl)-2'-deoxyuridine-5'-triphosphates (AA-dUTP) by an amide linkage ( Figure S2 in the Supporting Information) to obtain 5-[3-(Z-Gln-Gly-amido)-1-(E)-propenyl]-2'-deoxyuridine 5'-triphosphate (Z-QG-dUTP, Scheme 1), and to subsequently prepare Z-QG-modified DNA by using the polymerase chain reaction (PCR). A UV-absorbance spectrum of Z-QG-dUTP showed absorbance maxima at 240 and 296 nm, which are representative of a pyrimidine ring modified with an exocylic double bond.…”
Section: Resultsmentioning
confidence: 97%
“…For the site-specific cross-linking of PfuAP and Z-QG-DNA probes using MTG, an acyl-acceptor tag sequence, MKHKGGGSGGGSGS (the underlined K is a cross-linkable site recognized by MTG) was fused to the N terminus of PfuAP (NK14-PfuAP, Figure S5 in the Supporting Information). [30] In a previous study, bacterial alkaline phosphatase (BAP) with an MKHKGS tag at the N and C termini were successfully linked to a 5'-end, Z-QG-labeled oligonucleotide by MTG at pH 8.0, [12] and the DNA-BAP conjugate retained both oligonucleotide and enzymatic function following MTG treatment. In this study, a Z-QG-DNA probe contains a number of Z-QG moieties on a strand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, chemical modifications using bifunctional linkers has been widely used to covalently cross-link DNA and protein (Niemeyer 2001(Niemeyer , 2002. Recently, the site-specific syntheses of DNA-protein conjugates have been reported using expressed protein ligation (EPL) (Takeda et al 2004) and by transglutaminase (Tominaga et al 2007) to prevent inactivation and heterogeneous modification of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Using our enzymatic method for labeling of A*-Zmab with DNA, it was possible to produce the maximum level of protein-DNA conjugates within 15 min at 37 • C without any modification of DNA or protein. This novel strategy is about 15-60 times faster than those previously reported for protein-DNA conjugation strategies, suggesting that significant acceleration of the reaction rate could be achieved via this enzymatic covalent method [73][74][75][76]. In addition, the enzymatic covalent method used to conjugate synthetic DNA and the A*-Zmab fusion protein, is precise and well-controlled.…”
Section: X174 Gene A* Protein-mediated Covalent Couplingmentioning
confidence: 87%